Building a Culture of Ethics: The Impact of School-Based Counseling on Student Behavior - Hasan Sastra Negara; Marisalia Marisalia; Pradita Dien Ayu Putri Zamil; Susanti Susanti; Tania Inge Lodra (Smart Society, 2023)
The formation of character and ethics is crucial from childhood, as children easily absorb behaviors and values from their surroundings. Ethics is an integral part of human attitudes and interactions, which do not develop naturally but are shaped through guidance, education, and social influence from parents, teachers, and the community. Instilling ethical awareness at an early age is essential to fostering responsible and respectful individuals. This study aims to cultivate ethical awareness among children in Sidomulyo Village through a counseling-based approach conducted at SDN 07 Mesuji as part of a KKN (Real Work Lecture) program. The counseling method involves interactive discussions and role-playing activities designed to reinforce moral values and social etiquette.The findings indicate that this counseling approach leads to a noticeable improvement in the ethical behavior of the children in Sidomulyo Village. The program's effectiveness is evident in the children's increased understanding and application of moral values in daily interactions. These results suggest that structured ethical counseling can be a valuable tool in character education when supported by teachers, parents, and the school community.